ANTIOXIDANT ACTIVITY OF PIPPERIC ACID ESTERS SYNTHESIZED FROM PIPER NIGRUM - Ruiz Martel, Candy (2024)
The present study aims to develop new antioxidant candidates prepared by hemisynthesis from piperine isolated from Piper nigrum fruits. The first derivative synthesized was piperic acid, with a yield of 2,55%, and from the latter were obtained: methyl piperate, ethyl piperate and isopropyl piperate with yields of 76,75 %, 88,93 % and 95,3 %, respectively. The isolated and synthesized molecules were characterized by infrared and mass spectrometry. Analysis of antioxidant activity by DPPH yielded IC50 values of 8,77; 2,75; 8,35; 0,30 and 0,12 mg/ml for piperine, piperic acid, methyl piperate, ethyl piperate and isopropyl piperate, respectively. These results indicate a significant improvement in antioxidant activity over the starting product, piperine.